Chapter 7 The Long Carry Landscapes and the Shaping of British Medical Masculinities in the First World War - Meyer, Jessica (Springer Nature, 2018)
For First World War stretcher bearers, wartime landscapes had a direct impact on the work they undertook. Trenches, shell holes, mud and sand all presented challenges to their ability to carry wounded men swiftly and safely from where they were injured to aid posts and beyond. At the same time, landmarks could assist bearers in navigating the landscape they worked in, enabling these men to develop particular skills in direction-finding. This chapter uses the diaries and memoirs of British stretcher bearers to examine experiences of carrying in a range of wartime landscapes. In exploring how different landscapes shaped the labour that bearers undertook and the physical and embodied nature of the bearer's relationship with the landscape, it interrogates the masculine status of these men as non-combatant servicemen to uncover some of the relationship between landscape and masculine service identity in wartime.